List of digitized anarchist periodicals : Lidiap - Eckhardt, Wolfgang (2013)
Since its foundation in 2013 lidiap has grown quickly and lists now 1419 checked items of digitized anarchist journals/newspapers from the past 150 years, that are available for free download on the internet. The new version 4.0 includes periodicals recently scanned by the 'Istituto per la storia della Resistenza' (Italy), the 'Centro Documental de la Memoria Histórica' (Spain) and by many more institutions, libraries, political associations, enthusiasts